2024
DOI: 10.1042/bst20230731
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state nuclear magnetic resonance in the structural study of polyglutamine aggregation

Patrick C.A. van der Wel

Abstract: The aggregation of proteins into amyloid-like fibrils is seen in many neurodegenerative diseases. Recent years have seen much progress in our understanding of these misfolded protein inclusions, thanks to advances in techniques such as solid-state nuclear magnetic resonance (ssNMR) spectroscopy and cryogenic electron microscopy (cryo-EM). However, multiple repeat-expansion-related disorders have presented special challenges to structural elucidation. This review discusses the special role of ssNMR analysis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 95 publications
(172 reference statements)
0
1
0
Order By: Relevance
“…A kinetically competing, N17-independent aggregation pathway also exists for Huntingtin exon 1 which resembles that of simple polyglutamine and dominates upon disruption of N17 association or its partial excision (Jayaraman et al 2012b). Notably, solid-state NMR experiments concluded that the core of Httex1 fibrils was structurally similar to simple polyglutamine fragments, comprising of an inter-digitating hydrogen bond network formed between adjacent layers of polyQ β-hairpins through glutamine sidechains while the flanking N17 remains helical (Sivanandam et al 2011; Hoop et al 2016; van der Wel 2024).…”
Section: Introductionmentioning
confidence: 99%
“…A kinetically competing, N17-independent aggregation pathway also exists for Huntingtin exon 1 which resembles that of simple polyglutamine and dominates upon disruption of N17 association or its partial excision (Jayaraman et al 2012b). Notably, solid-state NMR experiments concluded that the core of Httex1 fibrils was structurally similar to simple polyglutamine fragments, comprising of an inter-digitating hydrogen bond network formed between adjacent layers of polyQ β-hairpins through glutamine sidechains while the flanking N17 remains helical (Sivanandam et al 2011; Hoop et al 2016; van der Wel 2024).…”
Section: Introductionmentioning
confidence: 99%